Evaluation of a nutrition intervention in adolescents of an urban area in Greece: short- and long-term effects of the VYRONAS study. - Mihas, Constantinos; Mariolis, Anargiros; Manios, Yannis; Naska, Androniki; Arapaki, Angeliki; Mariolis-Sapsakos, Theodoros; Tountas, Yannis (Public Health Nutr, 2010)
OBJECTIVE: To assess the short-term (15-d) and long-term (12-month) effects of a school-based health and nutrition education intervention on diet, nutrition intake and BMI. DESIGN: The 12-week teacher-implemented intervention in combination with seminars organized for parents was aimed at improving children's diet and nutrition knowledge. The intervention took place between September 2007 and January 2008. The participants were randomized to two study groups, the intervention group (IG) and control group (CG), and were examined prior to the intervention on a variety of health knowledge, dietary, behavioural and anthropometric indices. The same measurements were collected 15 d and 1 year after the intervention. SETTING: All high schools in Vyronas, a densely populated district of Athens, Greece. SUBJECTS: The sample consisted of 191 students aged 12-13 years. RESULTS: Twelve months after the intervention, the programme was effective in reducing various indices in the IG compared with baseline findings (BMI: 23.3 (sd 2.8) v. 24.0 (sd 3.1) kg/m2, P < 0.001; daily energy intake: 8112.4 (sd 1412.4) v. 8503.3 (sd 1419.3) kJ/d, P < 0.001; total fat intake: 31.3 (sd 4.4) v. 35.4 (sd 4.7) % of daily energy, P < 0.001). Except for BMI, decreases in the aforementioned indices were also observed 15 d after the intervention. In addition, students of the IG reduced their weekly consumption of red meat and non-home-made meals and increased their frequency of fruit and breakfast cereal consumption. CONCLUSIONS: The beneficial effects of this nutrition education intervention among adolescents may highlight the potential of such programmes in the prevention of obesity.
Keywords: Adolescent; Anthropometry; Body Mass Index; Child; Child Nutrition Sciences; Diet; Dietary Fats; Energy Intake; Feeding Behavior; Female; Follow-Up Studies; Greece; Health Education; Health Knowledge, Attitudes, Practice; Health Promotion; Humans; Male; Obesity; Schools; Time Factors